Understanding Brain Plasticity in Learning Process - Yuliana, Yuliana (Universitas Terbuka, 2020)
Brain plasticity takes an essential part in the learning process and memory retaining. Brain plasticity is connected with myelin sheath development and oligodendrocyte plasticity. Dynamic myelination is attained through certain learning activities. Oligodendrocyte plasticity means changes of oligodendrocyte precursor cell number either increasing or decreasing. This review aims to reveal what learning style is better in optimizing learning capacity by understanding dynamic myelination, brain plasticity, oligodendrocyte plasticity, and learning process. The review paper was based on journal reading. Keywords for literature searching are